2009
DOI: 10.1136/oem.2009.049676
|View full text |Cite
|
Sign up to set email alerts
|

A new method to determine laterality of mobile telephone use in adolescents

Abstract: Objectives As more children use mobile (cellular) telephones, public anxiety grows about the possible adverse health effects of radiofrequency (RF) exposure upon developing nervous systems. Most epidemiological studies investigating the health effects of mobile telephones have relied on self-reports from questionnaires. While there are some validation studies investigating the accuracy of self-reported mobile phone use in adults and adolescents, self-reported laterality of use has not been validated at any age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Second, the smartphone app was installed on a regular modern smartphone. This made changes in phone use behaviour due to inconvenience about the phone model less likely 10. Still, the ‘non-Android users’ in our study, who used a smartphone provided by the study team, reported some changes in phone use behaviour, mainly an increase in data use.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Second, the smartphone app was installed on a regular modern smartphone. This made changes in phone use behaviour due to inconvenience about the phone model less likely 10. Still, the ‘non-Android users’ in our study, who used a smartphone provided by the study team, reported some changes in phone use behaviour, mainly an increase in data use.…”
Section: Discussionmentioning
confidence: 64%
“…This is one of the first studies that was able to assess the position in which the phone is held during voice calls, and to compare this with self-reported laterality. A previous study by Inyang et al 10 using hardware-modified phones among adolescents concluded that self-reported laterality was of limited value (κ=0.3), though it is not clear how they defined HMP-measured laterality. We made several important observations regarding laterality, which will have implications for modelling RF dose within the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used number of voice calls as exposure metric instead of duration of voice calls per week, because these have been found to be more accurate than the duration of calls. While studies on adolescents showed that adolescent recall of number of calls was moderate, self-report of duration of calls was poor in this age group 46 47. It would have been interesting to access more objective phone use data in calling records from providers to supplement the self-report calling data, however, it was not possible to access this information, mostly because adolescents in Australia chiefly use prepaid phones.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies of brain tumours and mobile phone use have used exposure surrogates, such as number and duration of calls, which are known to involve considerable random error3 and importantly for cancer studies may involve differential recall errors in more distant times 4. TCSE was presumed by the authors to represent a more biologically-relevant metric of RF exposure.…”
mentioning
confidence: 99%